Aspirin Eugenol Ester Protects Vascular Endothelium From Oxidative Injury by the Apoptosis Signal Regulating Kinase-1 Pathway - Huang, Mei-Zhou; Zhang, Zhen-Dong; Yang, Ya-Jun; Liu, Xi-Wang; Qin, Zhe; Li, Jian-Yong (Frontiers in Pharmacology, 2020)
Aspirin eugenol ester (AEE) is a new potential pharmaceutical compound possessing anti-inflammatory, anti-cardiovascular disease, and antioxidative stress activity. The pharmacological activities of AEE are partly dependent on its regulation of cell apoptosis. However, it is still unclear how AEE inhibits cell apoptosis on the basis of its antioxidative stress effect. This study aimed to reveal the vascular antioxidative mechanism of AEE in response to H2O2-induced oxidative stress in HUVECs and paraquat-induced oxidative stress in rats. In the different intervention groups of HUVECs and rats, the expression of ASK1, ERK1/2, SAPK/JNK, and p38 and the phosphorylation levels of ERK1/2, SAPK/JNK, and p38 were measured. The effects of ASK1 and ERK1/2 on the anti-apoptotic activity of AEE in the oxidative stress model were probed using the corresponding inhibitors ASK1 and ERK1/2. The results showed that in the HUVECs, 200 μM H2O2 treatment significantly increased the phosphorylation of SAPK/JNK and the level of ASK1 but decreased the phosphorylation of ERK1/2, while in the HUVECs pretreated with AEE, the H2O2-induced changes were significantly ameliorated. The findings were observed in vitro and in vivo. Moreover, inhibition of ASK1 and ERK1/2 showed that ASK1 plays a vital role in the protective effect of AEE on H2O2-induced apoptosis. All findings suggested that AEE protects the vascular endothelium from oxidative injury by mediating the ASK1 pathway.